2016
DOI: 10.17306/j.afs.2016.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Tapioca maltodextrin in the production of soft unripened cheese

Abstract: Background. An excessive consumption of fat has been associated with an increased risk of health problems such as obesity, diabetes and cardiovascular diseases. Cheese is a highly concentrated product which is rich in protein and minerals such as calcium and phosphorus and essential amino acids, therefore it is an important food in the diet. But low fat cheeses are usually characterized as having poor body and fl avour. Therefore, it is crucial to fi nd ways of improving the acceptability of the product. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 18 publications
3
7
0
Order By: Relevance
“…The increase of total solids may be attributed to high moisture content in the cheese made from different levels of fat. These results were in harmony with those reported [1] who stated that the total solids increase in the cheese curd made from UFC led to an increase in moisture binding capacity in comparison with the cheese curd made from concentrated SM. Similar results were obtained by [20] who studied the effect of different levels of soybean milk on the chemical composition of the cheese made from buffalo milk.Moreover, [21] and [22] who reported the same results.…”
Section: Discussion Effect Of Different Levels Of Fat On Chemicalsupporting
confidence: 91%
See 4 more Smart Citations
“…The increase of total solids may be attributed to high moisture content in the cheese made from different levels of fat. These results were in harmony with those reported [1] who stated that the total solids increase in the cheese curd made from UFC led to an increase in moisture binding capacity in comparison with the cheese curd made from concentrated SM. Similar results were obtained by [20] who studied the effect of different levels of soybean milk on the chemical composition of the cheese made from buffalo milk.Moreover, [21] and [22] who reported the same results.…”
Section: Discussion Effect Of Different Levels Of Fat On Chemicalsupporting
confidence: 91%
“…Result in Table ( 1) showed that the fat contents of the cheese samples significantly (P< 0.05) different in all treatments. The highest fat (13.99±1.27%) was found in cheese samples with 2.5% milk fat, while the lowest one (13.61±1.20%) was found in the cheese sample with 3% milk fat.Results in Table (2) illustrate the effect of different levels of fat on sensory characteristics of Sudanese low-fat cheese.…”
Section: Results Inmentioning
confidence: 95%
See 3 more Smart Citations